Racial/Ethnic Disparities in the Lifetime Risk of Chlamydia trachomatis Diagnosis and Adverse Reproductive Health Outcomes Among Women in King County, Washington. (5th March 2018) - Chambers, Laura C; Khosropour, Christine M; Katz, David A; Dombrowski, Julia C; Manhart, Lisa E; Golden, Matthew R
Abstract : In this life table analysis, 1 in 5 women in King County, Washington, had chlamydia by age 34 years. Black women had a higher risk than white and Hispanic women. One in 1667 women is estimated to develop chlamydia-associated tubal factor infertility. Abstract: Background: Chlamydia trachomatis is the most common reportable infection in the United States and can cause pelvic inflammatory disease (PID) and tubal factor infertility (TFI). Methods: We created life tables to estimate the "lifetime" risk of chlamydia diagnosis among women aged 15–34 years in King County, Washington, between 1992 and 2014. We estimated the lifetime risk of chlamydia-associated PID and TFI incorporating published estimates of the risk of sequelae. Results: There were 51464 first chlamydia diagnoses in 1992—2014. For women born between 1980 and 1984, the lifetime risk of chlamydia diagnosis was 19.8% overall and 14.0% for non-Hispanic white, 64.9% for non-Hispanic black, and 32.6% for Hispanic women. The cumulative risk of chlamydia by age 24 increased overall from 13.9% to 17.3% among women born between 1975 and 1994 but declined among non-Hispanic black women, among whom risk by age 24 declined from 57.3% among women born between 1980 and 1984 to 38.6% among women born between 1990 and 1994. The lifetime risk of chlamydia-associated PID among women born between 1980 and 1984 ranged from 0.33% to 1.14%. Among non-Hispanic white, non-Hispanic black, and Hispanic women, the lifetime risk of chlamydia-associated TFI was 0.04%, 0.20%, and 0.10%, respectively. Conclusions: Over 60% of non-Hispanic black women had at least 1 chlamydia diagnosis by age 34 in the birth cohorts most affected, a risk almost 5 times that in non-Hispanic whites. An estimated 1 in 500 non-Hispanic black women develops chlamydia-associated TFI. More effective control measures are needed.